Regression Analysis on the Effect of Digital Reporting on the Quality of Financial Transparency - Prasetyo, Ardhani; Wibowo, Citra Lestari (Universitas Sains dan Teknologi Komputer, 2025)
The digital transformation in accounting has completely revolutionized the preparation and presentation of financial statements for companies. Especially in the age of information openness, digital reporting has been recognized as a tactical tool to improve transparency and accountability. This research aims to empirically evaluate the impact of digital reporting on the quality of financial transparency among publicly listed companies in Indonesia. The study uses a quantitative method that applies multiple linear regression to the second data set of 120 companies registered at the Indonesia Stock Exchange from 2020 to 2024. The independent variable digital reporting is assessed by XBRL adoption level, data accessibility, and update frequency, while financial transparency refers to the reporting being complete, reliable, and timely. The results indicate a notable and favorable impact of digital reporting on financial transparency (β = 0.708; p < 0.01), with an R² of 0.615. This suggests that the more the reporting is done digitally, the better the quality of financial disclosure. The research reaffirmed the role of digital reporting as an accountability tool that backed up the application of signaling theory in the context of digital reporting. The major benefit of this study is the provision of empirical evidence of the direct connection between digitalization and financial transparency in a still-developing country, thereby laying a basis for regulators and management to reinforce policies on technology-based reporting.